Prevalence, Risk, and Protective Factors of Internet Addiction Among Left-Behind Children: A Systematic Review and Meta-Analysis. - Zhang, Yu; Sun, Weiyi; Chao, Miao; Gu, Lijia; Yang, Haibo (International Journal of Mental Health & Addiction, 2026)
The internet addiction (IA) of left-behind children (LBC) has raised concern in China. However, the extent of LBC's susceptibility to IA remains a subject of debate, and a comprehensive understanding of the associated risk and protective factors is lacking. This systematic review and meta-analysis aims to summarize and synthesize the prevalence, risk, and protective factors of IA among LBC. A thorough search was conducted across multiple databases, including PubMed, Web of Science, EMBASE, PsycINFO, ProQuest, Scopus, the Chinese National Knowledge Infrastructure (CNKI), WanFang, and VIP, for eligible studies published before April 2024. The analysis included 38 studies on IA among LBC, comprising a total sample of 38,410 participants. The findings indicate that the prevalence of IA was 15%, with 1.37 times increase in IA risk compared to non-LBC. Maladaptive cognitions (r = 0.47, p < 0.01) and negative interpersonal relationships (r = 0.49, p < 0.01) identified as the strongest personal and social risk factors. Conversely, positive emotions/mood (r = -0.33, p < 0.01) and positive interpersonal relationships (r = -0.16, p < 0.01) were identified as the most significant personal and social protective factors. It is essential to develop targeted prevention and intervention strategies based on risk and protective factors to effectively address IA among LBC.